2021
DOI: 10.1177/00220345211009463
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Macrophages in Old Mice to Periodontal Disease

Abstract: The prevalence of periodontal disease increases with age. Systemic inflammatory dysregulation also increases with age and has been reported to contribute to the myriad of diseases and conditions that become more prevalent with advanced age. As periodontal disease involves a dysregulated host inflammatory response, the age-related inflammatory dysregulation may contribute to the pathogenesis of periodontal disease in aging populations. However, our understanding of what drives the age-related inflammatory dysre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 29 publications
0
27
0
Order By: Relevance
“…Many studies have used the periodontitis model by placing ligatures inoculated with P. gingivalis around the teeth of the mice to induce massive local accumulation of periodontal pathogens [10,[177][178][179][180][181][182][183][184][185][186][187][188]190,191,194,195]. In a representative study using this model, Li and Amar [188] provided evidence that the mouse periodontal model involving a ligature inoculated with P. gingivalis exhibited a more adequate inflammatory response and greater periodontal tissue breakdown than the control group, which induced periodontitis by ligature alone.…”
Section: Periodontitis Model Induced By Ligature Inoculated With P Gingivalismentioning
confidence: 99%
“…Many studies have used the periodontitis model by placing ligatures inoculated with P. gingivalis around the teeth of the mice to induce massive local accumulation of periodontal pathogens [10,[177][178][179][180][181][182][183][184][185][186][187][188]190,191,194,195]. In a representative study using this model, Li and Amar [188] provided evidence that the mouse periodontal model involving a ligature inoculated with P. gingivalis exhibited a more adequate inflammatory response and greater periodontal tissue breakdown than the control group, which induced periodontitis by ligature alone.…”
Section: Periodontitis Model Induced By Ligature Inoculated With P Gingivalismentioning
confidence: 99%
“…Since MSM is an anti-inflammatory compound, injection of MSM may have reduced the inflammatory events in the mandibular area and improved bone density. Clark et al reported depletion of macrophages in old mice resulted in decreased inflammatory cytokines within the gingiva and reduced bone loss ( Clark et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Clark et al. found that expressions of M1-related markers and proinflammatory cytokines and chemokines were significantly increased in elderly mice ( 42 ); found in their follow-up study of periodontal tissue, while elderly group and young group of mice in different period, there was no significant difference between the number of macrophages, but the elderly mice depleted macrophages more quickly in recovery stage ( 43 ). Although the depletion of macrophages stops inflammation earlier, it remains to be seen whether the process of tissue rebuilding and healing will also stop earlier.…”
Section: Overview Of Macrophages In Periodontal Tissuementioning
confidence: 99%